A Review of Fetal Bovine Serum in the Culture of Mesenchymal Stromal Cells and Potential Alternatives for Veterinary Medicine - Pilgrim, Cara R.; McCahill, Kiera A.; Rops, Jenna G.; Dufour, Jaustin M.; Russell, Keith A.; Koch, Thomas G. (Frontiers in Veterinary Science, 2022)
Fetal bovine serum (FBS) remains widely used as a supplement in cell culture media used in the isolation and expansion of mesenchymal stromal cells (MSC) despite longstanding practical, clinical, and ethical concerns over its use. As a result, research on alternative culture media supplement solutions that conserve crucial MSC characteristics has become increasingly relevant. Species-specific supplements and serum-free media such as platelet lysate or chemically defined media have been assessed for their effect in MSC cultures regarding proliferation, differentiation, and immunomodulatory capacity. While none of the alternatives offer a complete solution in replacing traditional FBS supplemented media for culturing MSCs for all species, short-term or transitional use of FBS-free media can perform equally well and could address some of the concerns over the use of FBS.